The Masorah of Elijah ha-Naqdan: An Edition of Ashkenazic Micrographical Notes - Attia, Élodie (Materiale Textkulturen, 2015)
Machine generated contents note: Masoretic Contents versus Masoretic Layout? -- What is a Figurative Masorah (Masora Figurata)? -- Why Edit Figurative Masorah? -- Critical Editions of Masoretic Notes -- Structure of the Edition -- Editorial Steps for Masoretic Micrographical Notes -- The Manuscripts of the Critical Apparatus -- Expected Results -- Edition -- Editorial Rules -- Important Remarks to the Reader -- Case 1 f. 63v, Genesis 50:21-Exodus 1:10 -- Case 2 f. 67bis r, Exodus 5:4 -- 5:15 -- Case 3 f. 72v, Exodus 9:34 -- 10:8 -- Case 4 f. 75v, Exodus 12:7 -- 12:17 -- Case 5 f. 77v, Exodus 13:7 -- 13:19 -- Case 6 f. 85v, Exodus 20:25 -- 21:11 -- Case 7 f. 89v, Exodus 24:9 -- 25:3 -- Case 8 f. 93r, Exodus 26:19 -- 26:32 -- Case 9 f. 98r, Exodus 30:1 -- 30:14 -- Case 10 f. 100v, Exodus 32:13 -- 32:25 -- Case 11 f. 101r, Exodus 32:26 -- 33:1 -- Case 12 f. 104r, Exodus 35:1 -- 35:15 -- Case 13 f. 113r, Exodus 40:37 -- Leviticus 1:10 -- Concluding Remarks -- Appendices -- Appendix 1 Categories of Masoretic Notes According to Shape -- Appendix 2 MS Vatican, Biblioteca Apostolica Vaticana, Vat. Ebr. 14 -- Appendix 3 MS Berlin, Staatsbibliothek zu Berlin, Or. Quart. 9 -- Appendix 4 Statistical Results -- Index of Hebrew Manuscripts -- Index of Biblical Verses and Occurrences -- Subject Index -- Plates
Keywords: Elijah ben Berechiah -- ha-Naqdan -- active 13th century -- Knowledge -- Masorah; Biblioteca apostolica vaticana -- Manuscript -- Vat. ebr. 14; Bible -- Exodus -- Selections -- Criticism, Textual; Schriftkunst; Bibel / Altes Testament; Bibel / Exodus; Hebräisch; Elijah ben Berechiah <ha-Naqdan>